Community-Based AI Pedagogical Literacy: A Case Study of AI Adoption in Teacher Professional Communities - Muhamad Handar; Shani Ramadhan Rasyid; Nur Indah Kumala (Jogjakarta Communication Conference (JCC), 2026)
The rapid development of artificial intelligence (AI), particularly generative AI technologies, has transformed the educational communication ecosystem and reshaped how knowledge is produced, distributed, and interpreted in learning environments. In the context, teachers play important roles not only as users of technology but also as mediators of knowledge and facilitators of pedagogical communication in digitally mediated classrooms. Although research on AI literacy in education continues to grow, many studies emphasize students’ competencies or institutional technology adoption, while limited attention has been given to how teachers collectively interpret and adopt AI within professional learning communities. To position this study within the existing research landscape, a bibliometric analysis using Publish or Perish and VOSviewer was conducted with the keywords “community-bases learning” and “digital literacy teachers.” The mapping highlights the central role of community interaction in connecting teachers’ digital literacy development with pedagogical practices. This study adopts a qualitative case study approach focusing on members of the Persatuan Guru Nahdlatul Ulama (Pergunu) in Bekasi City who participated as beneficiaries in the “AI Ready” AI literacy initiative. Data were collected through in-depth interviews, focus group-discussion, and documentation of training activities. The study examines how teachers interpret, negotiate, and collaboratively integrate AI tools into teaching practices, highlighting the role of professional communities in foresting meaningful AI adoption in education.